SPECIES DIVERSITY OF TRICHOSANTHES IN GUNUNG HALIMUN NATIONAL PARK - RUGAYAH, RUGAYAH (Research Center for Biology-Indonesian Institute of Sciences, 2001)
Inventory Trichosanthes L. in Gunung Halimun Nasional Park have been conducted. Seven species recorded occuring in TN Gn.Halimun namely, T. montana, T. ovigera, T. pubera, T. quinquangulata, T. tricuspidata, T. villosa, and T. wawrae.These species are found mostly in humid area in edge forest, or along river sides. Trichosanthes wawrae was found in Cikaniki,whereas the other six species found in Corridor Cianten. Trichosanthes quinquangulata has widelydistributed, it has found in Cibanteng and Leuwijamang as well. Exploration is still continuing to study the distribution of this genus in Gn. Halimun, to recollect the rare species and to do phylogenetic analysis.